Septins as membrane influencers: direct play or in association with other cytoskeleton partners - Benoit, Béatrice; Poüs, Christian; Baillet, Anita (Frontiers in Cell and Developmental Biology, 2023)
The cytoskeleton comprises three polymerizing structures that have been studied for a long time, actin microfilaments, microtubules and intermediate filaments, plus more recently investigated dynamic assemblies like septins or the endocytic-sorting complex required for transport (ESCRT) complex. These filament-forming proteins control several cell functions through crosstalks with each other and with membranes. In this review, we report recent works that address how septins bind to membranes, and influence their shaping, organization, properties and functions, either by binding to them directly or indirectly through other cytoskeleton elements.